Treatment outcomes and associated factors of stroke in Ethiopia: a systematic review and meta-analysis - Addisu Getie; Shirin Jahan Mumu; Amit Arora (BMC Cardiovascular Disorders)
Abstract Introduction Stroke is characterized by a sudden onset of focal or global neurological deficits resulting from reduced cerebral blood flow. Poor treatment outcomes are primarily caused by uncontrolled blood pressure and delayed hospital arrival. Despite Ethiopia’s progress toward universal health coverage, stroke remains a significant burden, accounting for 6.23% of total deaths in 2017. This systematic review and meta-analysis aimed to evaluate the treatment outcomes and associated factors of stroke in Ethiopia. Methods HINARI, EMBASE (Ovid), Scopus, PubMed, African Journals Online (AJOL), gray literature, and published and unpublished articles from the Ethiopian University repository were searched. Cochrane I2 statistics and Egger’s test with funnel plot were done to check heterogeneity and publication bias respectively. Subgroup analysis, meta-regression, and sensitivity analysis were computed to investigate the source of heterogeneity. A log odds ratio was employed to ascertain the association between poor (stroke patients who died or were discharged with significant functional and structural dysfunction) stroke treatment outcomes and associated factors. A statistical test with a p-value of less than 0.05 was considered statistically significant. Result Of 10,377 studies identified across all databases, a total of 38 studies were included in this review with a total of 10,074 participants. The overall pooled prevalence of poor treatment outcomes (death and discharge with physical and functional impairment) in stroke patients was 30.18% (95% CI: 23.92–36.44), with 22.61% (95% CI: 17.94–27.29) resulting in death. Conversely, 53.39% (95% CI: 47.00–59.78) of patients had good treatment outcomes. The Oromia region had the highest prevalence of poor outcomes at 39.25% (95% CI: 28.48 − 50.03%), while the Sidama region reported the highest rate of good outcomes (discharged without any physical and functional impairment) at 85.30% (95% CI: 79.86 − 90.74%). Factors contributing to poor treatment outcomes included illiteracy: AOR 21.29, hemorrhagic stroke type: AOR 2.92, longer hospital stays: AOR 1.67, delayed hospital arrival: AOR 4.67, and comorbidities: AOR 2.55. Conclusion This review reveals significant variability in stroke treatment outcomes across Ethiopia. The Oromia region had the highest poor outcomes, while the Sidama region reported the best outcomes. To improve outcomes, public awareness campaigns should focus on early detection and hospital arrival.